The prosocial psychopath: Explaining the paradoxes of the creative personality - Galang, Adrianne John R. (Animo Repository, 2010)
The literature on the creative personality is curiously equivocal in its characterization of the traits supposedly possessed by eminent creators. While acclaimed as revolutionary and pioneering visionaries, the same category of people can come across as unsocialized and discomfiting even to their close associates and admirers. This paper suggests that these ambiguities can be addressed by appealing to the potential psychobiological mechanisms that can give rise to the expression of both creative ability and " antisocial" traits. Work on latent inhibition, the somatic marker hypothesis, Eysenck's biosocial theory of crime and the dopamine hypothesis of addiction are reviewed and integrated into a model that examines the role of dopamine as a critical agent in the creative personality system. Finally, testable hypotheses stemming from the model are proposed. © 2010 Elsevier Ltd.